2014
DOI: 10.1103/physreve.89.062811
|View full text |Cite
|
Sign up to set email alerts
|

Disorder induces explosive synchronization

Abstract: We study explosive synchronization, a phenomenon characterized by first-order phase transitions between incoherent and synchronized states in networks of coupled oscillators. While explosive synchronization has been the subject of many recent studies, in each case strong conditions on either the heterogeneity of the network, its link weights, or its initial construction are imposed to engineer a first-order phase transition. This raises the question of how robust explosive synchronization is in view of more re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 44 publications
1
74
0
Order By: Relevance
“…(1) for = 0 and 15 on a network of size N = 1000 constructed using the configuration model [38]. We note that, similar to the C. elegans network and the SE network, in the absence of disorder the transition from incoherence to synchronization 0.5 0.7 0.9 1. transitions can be induced for cases in which the phase transitions are continuous under the condition ω i = k i if ε is large enough [248]. The effect of addition of disorder on the order parameter r can be seen in Fig.…”
Section: B Scale-free Networkmentioning
confidence: 97%
See 1 more Smart Citation
“…(1) for = 0 and 15 on a network of size N = 1000 constructed using the configuration model [38]. We note that, similar to the C. elegans network and the SE network, in the absence of disorder the transition from incoherence to synchronization 0.5 0.7 0.9 1. transitions can be induced for cases in which the phase transitions are continuous under the condition ω i = k i if ε is large enough [248]. The effect of addition of disorder on the order parameter r can be seen in Fig.…”
Section: B Scale-free Networkmentioning
confidence: 97%
“…The effect of addition of disorder to disturb the frequency assignment ω i = k i was further analyzed by Skardal and Arenas [248] for more heterogeneous structures, namely for SF and stretched exponential networks with a degree distribution given by…”
Section: -2mentioning
confidence: 99%
“…We look for the linear stability spectrum of eigenmodes around a fixed point by adding the perturbations discussed into (13), and collecting terms of order η:…”
Section: Stability Analysis and Bifurcationsmentioning
confidence: 99%
“…Our approach is narrowly confined to how random interactions lead to some form of weak emergence due to feedbacks 6,28,50 . Even though noise provides additional degree's of freedom that are important for adaption 17 , it has been shown that by adding uncorrelated noise to oscillators one can induced explosive synchronization, i.e., very sharp phase transitions 76,98 . Barabási and Albert show that for sufficiently heterogeneous network topologies, simple correlations can induce explosive phase transitions 15 .…”
Section: Emergencementioning
confidence: 99%